Characterisation of Polacrylate-Polysacharide System. Part I. Infrared Structural Studies - Kaczmarska, Karolina; Śmietana, Mateusz; Drożyński, Dariusz; Woźniak, Faustyna; Bobrowski, Artur (Journal of Casting & Materials Engineering, 2024)
For the prepared polymer systems based on an poly(acrylic acid) and a colloidal solution of native starch, a series of IR (FTIR) structural studies and tests under heating conditions (ATR-FTIR) were carried out. Two components from the group of native starch of different biological origin (potato, cassava) were selected. The analysis of the collected results was aimed at assessing the effect of the biological origin of the starch on the structure, thermal sensitivity of the acrylic polymer-based system. On the basis of interaction effects occurring in the obtained synthetic polymer-natural polymer systems, the validity of mixing selected components to obtain composition was verified.